Meningkatkan Sikap Kepedulian Lingkungan Anak melalui PjBL(Project Based Learning) membuat Ecobrick pada usia 5-6 Tahun di TKQ An-Namlu - Ajijah, Milah Nur (Peneliti.net, 2025)
The purpose of this study is to explain the learning process and outcomes of children aged 5-6 years at TKQ An Namlu Palumbonsari Karawang by using the PjBL (Project Based Learning) learning model in improving environmental awareness attitudes. This study uses classroom overlay research with the Kemiis and Mc taggart models which include overlap, planning, observation and evaluation. This research consists of two cycles with cycle I six meetings and cycle II five meetings. In these two cycles, data analysis is carried out using qualitative and quantitative data techniques. Quantitative data analysis was carried out by looking at data from observation records, interview records and documentation records. Quantitative data analysis was carried out through descriptive statistics by comparing the results obtained from pre-collision, cycle I and cycle II. The results of this research show that there is an increase in environmental awareness attitudes, as evidenced by the data obtained at the time of pre-overlap, the percentage reached 42.29% and increased by 14.17% so that in the first cycle it got a score of 56.46% and in the second cycle it increased again by 26.58% with a result of 83.04%. Keywords: Environmental Concern Attitude, PjBL (Project Based Learning) Learning Model, children aged 5-6 years